Lectins modulate the functional properties of GluN1/GluN3-containing NMDA receptors - Hemelikova, Katarina; Kolcheva, Marharyta; Skrenkova, Kristyna; Kaniakova, Martina; Horak, Martin (Neuropharmacology, 2019)
N-methyl-d-aspartate receptors (NMDARs) play an essential role in excitatory neurotransmission within the mammalian central nervous system (CNS). NMDARs are heteromultimers containing GluN1, GluN2, and/or GluN3 subunits, thus giving rise to a wide variety of subunit combinations, each with unique functional and pharmacological properties. Importantly, GluN1/GluN3A and GluN1/GluN3B receptors form glycine-gated receptors. Here, we combined electrophysiology with rapid solution exchange in order to determine whether the presence of specific N-glycans and/or interactions with specific lectins regulates the functional properties of GluN1/GluN3A and GluN1/GluN3B receptors expressed in human embryonic kidney 293 (HEK293) cells. We found that removing putative N-glycosylation sites alters the functional properties of GluN1/GluN3B receptors, but has no effect on GluN1/GluN3A receptors. Moreover, we found that the functional properties of both GluN1/GluN3A and GluN1/GluN3B receptors are modulated by a variety of lectins, including Concanavalin A (ConA), Wheat Germ Agglutinin (WGA), and Aleuria Aurantia Lectin (AAL), and this effect is likely mediated by a reduction in GluN1 subunit-mediated desensitization. We also found that AAL has the most profound effect on GluN1/GluN3 receptors, and this effect is mediated partly by a single N-glycosylation site on the GluN3 subunit (specifically, N565 on GluN3A and N465 on GluN3B). Finally, we found that lectins mediate their effect only when applied to non-activated receptors and have no effect when applied in the continuous presence of glycine. These findings provide further evidence to distinguish GluN1/GluN3 receptors from the canonical GluN1/GluN2 receptors and offer insight into how GluN1/GluN3 receptors may be regulated in the mammalian CNS.
Keywords: Glycosylation; glycin; Protein Subunits; Receptors, N-Methyl-D-Aspartate; podjednotky proteinů; Glycine; Membrane Potentials; Desensitization; Posttranslational modification; Humans; receptory N-methyl-D-aspartátu; Protein Binding; Patch-clamp technique; lidé; Cells, Cultured; Glutamate receptor; membránové potenciály; glykosylace; kultivované buňky; polysacharidy; Polysaccharides; vazba proteinů; Lectins; Ion channel; lektiny